Effect of long-term starvation and restricted feeding on growth performance and body composition of juvenile Siberian sturgeon (Acipenser baerii Brandt 1869) - S. Shirvan; B. Falahatkar; H. Noveirian; A. Abasalizadeh* (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2013)
The present study was designed and performed to investigate the eefect of long-term some feeding strategies (starvation, restricted feeding at rate of 1% biomass per tank and satiate feeding as control) on growth performance and body composition of juvenile Siberian sturgeon (Acipenser baerii Brandt 1869) for 8 weeks. In this regard, 270 juveniles Siberian sturgeon (average weight 54 Â± 6/27 g and density 1.5 g/l) were distributed in three treatments (with three replicates) in 9 fiberglass tanks (1050 l). For all fish in each tank, body weight and total length were individually recorded at a biweekly interval. At the termination of the experiment period, five fish per replicate were caught randomly for proximate composition. Results showed that growth performance of Siberian sturgeon was affected significantly by starvation and restricted feeding periods. Moisture and lipid contents were differed significantly in all treatments which the highest moisture and lipid contents were observed in starved and control fish, respectively. Protein content in starved fish was significantly lower than other groups, whereas ash contents were not significantly different among the treatments. In general, weight loss and other growth factors of juveniles siberian sturgeon during the food shortage were refered to mobilizing the body lipid reservesand then body protein sources and replacing with water. In fact, juvenile Siberian sturgeon can conserve body protein stores better than lipids during the food shortage period